Cancer incidence in patients with type 2 diabetes mellitus: a population-based cohort study in Shanghai. Issue 1 (December 2015) - Xu, Hui-Lin; Fang, Hong; Xu, Wang-Hong; Qin, Guo-You; Yan, Yu-Jie; Yao, Bao-Dong; Zhao, Nai-Qing; Liu, Yi-Nan; Zhang, Fen; Li, Wei-Xi; Wang, Na; Zhou, Jie; et al.
Abstract Background Type 2 diabetes mellitus (T2DM) has been suggested to increase the risk of cancers. The aim of this study was to investigate the risk of common cancers in Chinese patients with T2DM. Methods A population-based retrospective cohort study including 36, 379 T2DM patients was conducted in Minhang District of Shanghai, China, during 2004 to 2010. All T2DM patients were enrolled from the standardized management system based on local electronic information system. Newly-diagnosed cancer cases were identified by record-linkage with the Shanghai Cancer Registry. Standardized incidence ratios (SIR) and 95 % confidence interval (CI) were used to estimate the risk of cancers among T2DM patients. Results Overall crude incidence rate (CIR) of cancers was 955.21 per 105 person-years in men and 829.57 per 105 person-years in women. Increased risk of cancer was found in both gender, with an SIR being 1.28 (95 % CI = 1.17–1.38) in men and 1.44 (95 % CI =1.32–1.55) in women. Increased risk of colon (SIR = 1.97; 95 % CI = 1.49 to 2.46), rectum (1.72; 1.23 to 2.21), prostate (2.87; 2.19 to 3.56), and bladder cancers (1.98, 1.28 to 2.68) were observed in men and elevated risk of colon (1.67; 1.25 to 2.08), breast (1.66; 1.38 to 1.95), and corpus uteri cancers (2.87; 2.03 to 3.71) were observed in women. Conclusions Our results indicate that Chinese patients with T2DM may have an increased risk of some cancers, and the increase may vary by sub-sites of cancers.